I.T. asset management system for transport and logistics company - Jasmin, Alieha Benedict A.; Martin, Carl Michael B.;Roque, Mary Grace D.;Salazar, Jher Carlson D. (Manila : National University, 2017)
I.T. Asset Management System for Transport and Logistics Company is an intranet based application that is designed to give convenient way in managing and requesting of asset for the employees of Transport and Logistics Company.
Title page -- Recommendation for oral examination -- Approval sheey/Panel of evaluators and examiners -- Grammarian's certificate -- Dedication -- Acknowledgement -- Executive summary -- Table of contents -- List of figures -- List of tables -- Chapter I: Introduction -- Chapter II: Review of related literature -- Chapter IIITechnical background -- Chapter IV: Methodology, results and discussions -- Chapter V: Summary and recommendation -- References -- Appendices.
Includes bibliographical references.